Stories of transformation - Lotz-Sisitka, Heila, 1965- (International journal of sustainability in higher education, 2004)
Introduces the special issue on "Stories of transformation" in higher education (HE). Highlights that transformation in HE involves multi-disciplinary and applied orientations to curriculum change, which break down the modernist dichotomy of theory and practice. Also highlights the significance of change processes that are value-based and require the involvement of committed individuals and groups that are prepared to engage the often rhetorical nature of declarations and institutionalized commitments to sustainable development. Also highlights the absence of theorizing about change and action.